Tooth loss in periodontally compromised patients: Results 20 years after active periodontal therapy - Pretzl, Bernadette; El-Sayed, Shirin; Kronsteiner, Dorothea; Eickholz, Peter; Bäumer, Amelie (Journal of clinical periodontology, 2018)
Aim - To assess tooth loss in periodontally compromised patients 20 years after active periodontal therapy (APT) and to detect potential influencing factors for tooth loss on patient level. - - Material...